2
$\begingroup$

Problem is ring isomorphism from $\mathbb Z_3\times \mathbb Z_2$ to $\mathbb Z_6$.

My solution:

Let $f=\mathbb Z_3\times \mathbb Z_2 \to \mathbb Z_6$ defined as $f(a_3,b_2)=ab_6$.

I prove it is isomorphism:

It is obviously that $|\mathbb Z_6|$=$|\mathbb Z_3\times\mathbb Z_2 |$ (the same cardinality). Surjectivity is obviously because of the Chinese Remainder Theorem.

Injectivity : Let $f(a_3,b_2)=f(c_3,d_2)$. Then $f(a_3-c_3,b_2-d_2)=f(a_3,b_2)-f(c_3,d_2)=0$. If $f(a_3,b_2)=ab_6=0_6$ then because a_2 is divisible by 2 and b_3 by 3, then ab_6 is divisible by 6. Therefore ab_6=0.

It is correct ? Thanks

$\endgroup$
  • 2
    $\begingroup$ This is not a homomorphism for addition. $\endgroup$ – Bernard Mar 20 '16 at 0:01
  • 1
    $\begingroup$ It does not define a function either. $1_2=3_2=b_2$, $0_3=3_3=a_3$, but $(0\cdot1)_6\ne(3\cdot3)_6$. $\endgroup$ – user228113 Mar 20 '16 at 0:09
0
$\begingroup$

The correct homomorphism is $$f(a_3,b_2)=(4a+3b)_6$$ See if you can prove this is a ring isomorphism.

$\endgroup$
  • $\begingroup$ The question asks "is this correct?" and this answer does not address that (even though there is plenty to say about the work the OP is asking about). $\endgroup$ – Milo Brandt Mar 20 '16 at 0:16
  • $\begingroup$ @Milo it's implied by my answer that it is not correct. You can post your own answer if you prefer a different approach. $\endgroup$ – Matt Samuel Mar 20 '16 at 0:18
  • $\begingroup$ @MattSamuel I have got a problem to prove it. Can you give me any hint ? $\endgroup$ – joeblack Mar 20 '16 at 11:27
  • $\begingroup$ @joe for example, the only way for $(4a+3b)_6$ to be 0 is if $2\mid b$ because we already have $2\mid 4a$. Thus in that case $b_2=0$. You can also show that $a_3$ must be 0, so it is injective. $\endgroup$ – Matt Samuel Mar 20 '16 at 15:05
2
$\begingroup$

Note that any ring homomorphism $\Bbb Z_6 \to \Bbb Z_2\times \Bbb Z_3$ is determined by the image of $1$. Consider mapping $1\to (1,1)$. This is an isomorphism. Indeed, it is injective since if $n\to (n,n)=(0,0)$ then $2,3$ divide $n$, and then so does $6$, hence $n=0$. Since both rings have six elements, this is a bijection. One readily checks this is a ring homomorphism, so the claim follows. The inverse mapping sends $(1,0) = 3(1,1)$ to $3$ and $(0,1) = 4(1,1)$ to $4$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.